Teachers’ Perspectives on Bullying Behaviors in Value-Based School Culture - Deniz, Afet; Kan, Şebnem Güldal (Journal of Posthumanism, 2025)
Bullying is defined as the situation in which an individual is exposed to negative behaviors that are repeated over time by another person or group. This situation is an important problem that negatively affects not only peer relationships but also teacher-student relationships. Bullying can occur in different types. These are classified as physical, verbal, social and psychological bullying. School culture can be defined as a dynamic structure created by school stakeholders (such as teachers, administrators and parents) within the framework of common values and rules. This culture directly affects students’ social development and behaviors in the school environment. In this context, Values Education is of great importance for children to develop positive behaviors and to adapt to their environment in a healthy way. Values Education contributes to both the individual development of students and ensures their integration with social values. In particular, the acquisition of social values plays an important role in reducing bullying behaviors. This study aimed to examine teachers’ views on bullying behaviors in a value-centered school culture. A case study, one of the qualitative research designs, was used in the study. Data were collected through a semi-structured interview form and a personal information form. The case study design is a method that aims to examine a specific event, phenomenon or social group in depth within its own context. The study group of the research consists of a total of 22 class and branch teachers working in primary schools and preschool education institutions affiliated with the Ministry of National Education of the Turkish Republic of Northern Cyprus. The participants were determined using the purposive sampling method. The obtained data were analyzed using the content analysis method. According to the research findings, it was determined that the value that teachers care most about instilling in their students in the school environment is respect. Love is second. In the light of this data, the scope of Values Education can be further expanded by including parental opinions in future studies.